PEDAGOGICAL EDUCATION IN THE REPUBLIC OF POLAND AS OBJECT OF INTERDISCIPLINARY RESEARCH - Hryshchuk, Yuliia (Continuing Professional Education: Theory and Practice, 2019)
The article examines the pedagogical education in the Republic of Poland as object of interdisciplinary research. This article analyzes the understanding of the term «pedagogical education» in polish scientific space. The complexity, contradiction and multidimensionality of perception and interpretation of the terms «education», «pedagogical education» by Polish and Ukrainian researchers are analyzed. An attempt to examine the term in terms of psychology, pedagogy, sociology, education policy and other fields of scientific knowledge. Polish researchers consider that pedagogy is an interdisciplinary discipline. In Polish scientific space concept «education» is undifferentiated, covering both education and training.In Polish scientific circulation do not use such concepts as«vocational pedagogical education». But рedagogical training is required for all qualified professionals professions such as «man – man». Ukrainian researchers analyze the pedagogical education as: system of training of pedagogical personnel, specialized subsystem of educational sphere, multidisciplinary and multidimensional process. It is concluded, that in Polish researches closest to the content of «pedagogical education» in the domestic space is the following concept: comprehensive training of teaching staff, which contributes to the need to be competitive in the labor market.